Beyond impunity: an evaluation of New York State's nonfatal shooting initiative - Cochran, Hannah (Criminology & public policy, 2022)
New York State's nonfatal shooting initiative provided support to police departments and district attorney's offices in two cities, Newburgh and Utica, NY: two investigators and a crime analyst dedicated to nonfatal shooting investigations, training and technical assistance, and timely forensic laboratory analysis of evidence. Evaluation findings show that the initiative positively affected the processes and outcomes of nonfatal shooting investigations. The immediate effect of the initiative was dramatic in Newburgh and less pronounced but noteworthy in Utica. In both sites, however, clearance rates declined over time, as caseloads grew. The initiative consisted of several components: a commitment to evidence-based prosecutions; investigative personnel dedicated to nonfatal shooting cases; collaboration between investigative and prosecutorial actors. The immediate effects of the initiative suggest how successful nonfatal shooting investigations can be when they are better resourced, while the decay in the impacts over time illustrate the need to ensure that the resources are commensurate with the caseload.